Does local economic uncertainty matter for risk of property companies? Evidence from US REITs - Song, Jeongseop (International Journal of Strategic Property Management, 2023)
With the growing number of publicly listed property companies worldwide, investors are increasingly interested in assessing the risks of such real estate companies in the stock market. This study aims to investigate the risk of US equity real estate investment trusts (REITs) in the local market context. Using US equity REITs data from 1997 to 2020, this study examines the impact of local economic uncertainty (LEU) on risk of REITs. To measure LEU, we first exploit textual analysis to extract geographical information from REITs’ annual financial reports (10-K filings) and construct state-level regional exposure for each firm. We then obtain LEU by incorporating the regional exposure with local market uncertainty based on locally headquartered firms. In the empirical results, we find that REITs with higher LEU are strongly and positively associated with higher future risks. This positive relationship is robust to a variety of alternative risk and LEU measures. Moreover, the effects of LEU are stronger for geographically concentrated REITs and LEU is positively priced by investors.